Mentalizing and Information Propagation through Social Network: Evidence from a Resting-State-fMRI Study - Zhang, Huijun; Mo, Lei (Frontiers in Psychology, 2016)
Microblogs is one of the main social networking channels by which information is spread. Among them, Sina Weibo is one of the largest social networking channel in China. Millions of users repost information from Sina Weibo and share embedded emotion at the same time. The present study investigated participants’ propensity to repost microblog messages of positive, negative or neutral valence, and studied the neural correlates during resting state with the reposting rate of each type microblog messages. Participants preferred to repost negative messages relative to positive and neutral messages. Reposting rate of negative messages was positively correlated to the functional connectivity of temporoparietal junction (TPJ) with insula, and TPJ with dorsolateral prefrontal cortex (DLPFC). These results indicate that reposting negative messages is related to conflict resolution between the feeling of pain/ disgust and the intention to repost significant information. Thus, resposting emotional microblog messages might be attributed to participants’ appraisal of personal and recipient’s interest, as well as their cognitive process for decision making.